Body-Centered Interventions for Psychopathological Conditions: A Review - Tarsha, Mary S.; Park, Sohee; Tortora, Suzi (Frontiers in Psychology, 2020)
World-wide, billions of dollars are spent each year on body-centered interventions to alleviate both physical and psychological pathologies. Given the high demand and increasing popularity of body-centered interventions, there is need for a systematic organization of empirical evidence associated with body-centered therapies. This article reviews the psychological effects of body-centered interventions on emotional well-being, including both self and other-administered (receptive) therapies. Theory behind body-centered interventions rely upon the bidirectional communication pathway between the brain and body. We investigated the bidirectional communication pathway between the brain and body by evaluating evidence across multiple body-centered therapies. The research reviewed includes studies that investigate effects of massage therapy, reflexology, acupuncture, functional relaxation, emotional freedom technique, Rolfing, yoga and dance/movement therapy on psychological conditions across the lifespan. Results demonstrated that overall, massage therapy, dance/movement therapy, functional relaxation, reflexology, acupuncture and emotional freedom technique seem to alleviate stress, depression, anxiety, bipolar disorder and facilitate pain reduction. Although these conclusions are limited by scarcity of high-quality empirical data and contradictory findings, available evidence indicates that body-centered interventions can be effective in reducing psychopathology and supports the proposed mechanism of the bidirectional pathway between the brain and body; the body holds the potential to influence the mind. Integrating body-centered therapies in both clinical settings and as self-care could lead to better outcomes. Lastly, we propose the first taxonomy of body-centered interventions and empirical evidence of their effectiveness for clinicians and researchers.